Analisis Evolusi Teori Elektromagnetisme dari Maxwell hingga Sekarang - Walfrid Zebua (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Electromagnetism is a fundamental pillar of physics, underlying numerous natural phenomena and modern technologies. This study analyzes the evolution of electromagnetic theory from the classical era of Maxwell, through the relativistic contributions of Einstein, to the quantum developments of Feynman. The theory has undergone three main phases: classical, relativistic, and quantum, each significantly advancing scientific understanding and technological innovation, including radio communication, lasers, fiber optics, and medical imaging technologies. The study also explores future challenges, such as addressing modern physics anomalies like dark matter and dark energy, and prospects for interdisciplinary integration to drive further advancements. These findings affirm the enduring relevance of electromagnetic theory in scientific and technological progress, establishing it as a critical foundation for future exploration and applications